Morphometric and histopathological findings in the adrenal glands of dogs with chronic diseases - Salvagni, Fernanda A.; Siqueira, Adriana de; Maria, Anna Carolina B. E.; Maiorka, Paulo C. (Brazilian Journal of Veterinary Pathology, 2017)
Prolonged stress suffered by the organism in the presence of chronic diseases can result in functional and morphological changes to the adrenal glands; although the effects of chronic stress on the adrenal gland function in live dogs is well documented, studies focusing on the morphologic changes in the adrenal glands have been lacking. Thus, this study aimed to identify and connect possible morphometric and histopathological changes in the adrenal glands of necropsied dogs in the presence or absence of chronic diseases. Morphological changes in the adrenal glands of 46 necropsied dogs were evaluated through morphometric and histopathological analyses. The morphometric characteristics of the adrenal glands of dogs were influenced more by the animal’s body weight (p < 0.0001) and adrenocortical hyperplasia (p < 0.05) than by the stress associated with chronic diseases or acute conditions. Previously healthy animals with sudden death or animals that died from acute diseases had significant severe congestion in the adrenal glands (p = 0.0272), while adrenocortical hyperplasia was more frequent in the chronic diseases group (p = 0.0041). Fibrosis at the corticomedullary junction (p < 0.0001) and inflammatory infiltrate (p = 0.0015) were observed only in animals with chronic diseases. The adrenal glands of dogs with chronic cardiac dysfunction frequently showed significant necrosis (p = 0.0256), fibrosis (p = 0.0002) and lipid depletion (p = 0.0288). Thus, while the weight or dimensions of the adrenal glands of dogs at necropsy should not be used alone as parameters to indicate a relation with the stress suffered prior to death, the histopathological findings could aid and support necropsy conclusions regarding the presence of chronic diseases.